Buying Lottery Tickets for Foreign Workers: Lost Quota Rents Induced by H-1B Policy - Rishi Sharma; Chad Sparber (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
The H-1B program allows firms in the United States to temporarily hire high skilled foreign citizens. The government restricts foreign labor inflows and therefore generates potential rents typical of a quota. However, the US allocates H-1B status by random lottery. We develop a theoretical model demonstrating that this lottery creates a negative externality by incentivizing firms to search for more workers than can actually be hired and, in so doing, completely destroys quota rents. Moreover, some firms specialize in hiring foreign labor and contracting out those workers' services to third-party sites, and this outsourcing behavior both exacerbates lost quota rents and leads to an increased concentration of H-1B workers among a small number of firms. Simple numerical exercises suggest that the H-1B lottery and outsourcing result in an annual economic loss exceeding 10,000 per new H-1B worker hired relative to what would occur under a quota alone.
Keywords: J61; J68; F22; 330; Skilled Workers; H-1B; Quota Rents; Outsourcing